11β-hydroxysteroid dehydrogenase type 1 gene expression is increased in ascending aorta tissue of metabolic syndrome patients with coronary artery disease - Atalar, F.; Vural, B.; Ciftci, C.; Demirkan, A.; Akan, G.; Susleyici-Duman, B.; Gunay, D.; Akpinar, B.; Sagbas, E.; Ozbek, U.; Buyukdevrim, A.S. (Genetics and molecular research, 2012)
11β-hydroxysteroid dehydrogenase type 1 (11β-HSD-1) activity and mRNA levels are increased in visceral and subcutaneous adipose tissues of metabolic syndrome subjects. We analyzed 11β-HSD-1 expression in human epicardial adipose (EA) and ascending aorta (AA) tissues of metabolic syndrome patients and examined their contribution to the development of coronary atherosclerosis. The 11β-HSD-1 expression was evaluated by qRT-PCR in EA and AA tissues of 20 metabolic syndrome patients with coronary artery disease (metabolic syndrome group) and 10 non-metabolic syndrome patients without coronary artery disease (controls). 11β-HSD-1 expression was increased in EA and AA tissues of the metabolic syndrome group (4.1- and 5.5-fold, respectively). A significant positive correlation was found between 11β-HSD-1 expression in EA tissue and waist hip ratio and 11β-HSD-1 expression in AA tissue and body mass index, while a negative correlation was found between 11β-HSD-1 expression in EA tissue and HDL. Expression of CD68, a macrophage marker, was significantly increased in both tissues of the metabolic syndrome group; it was 2-fold higher in AA tissue compared to EA tissue in the metabolic syndrome group. Our findings of increased expression of 11β-HSD-1 and CD68 in AA tissue of the metabolic syndrome group lead us to suggest that they contribute to coronary atherosclerosis in metabolic syndrome. This positive correlation between obesity markers and 11β-HSD-1 in AA and EA tissues strengthens the evidence that 11β-HSD-1 has a role in metabolic syndrome. To the best of our knowledge, this is the first report showing 11β-HSD-1 and CD68 expression in AA tissue of metabolic syndrome patients. We suggest that there is tissue-specific expression of 11β-HSD-1 in metabolic syndrome and associated cardiovascular disorders.